Community Empowerment Through Plastic Waste Recycling Skill (Case Study On The Bidarmu Waste Bank) - Rega Yulita; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the existence of plastic waste recycling activities in the community. The goal is to empower the community through skill activities so that they can increase knowledge, increase family income and prosper the people of Pasia Nan Tigo Village. The purpose of this study is to describe community empowerment through plastic waste recycling skills seen from the process, form and supporting and inhibiting factors in community empowerment.This research is using a qualitative approach, the research method is a case study. The sources of data in this study are the people of Pasia Nan Tigo Village who are members of the BIDARMU waste bank as research subjects and the head of the waste bank as research informants. Data collection techniques used in this study are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and drawing conclusions. The technique of data validity is by using triangulation of sources and methods.The results of the study show that (1), the process or stages of community empowerment are planning, implementation, mentoring and evaluation, (2), forms of community empowerment in the form of knowledge, independence and cooperation, (3), supporting factors are positive responses from members, active chairman, support family and availability of materials. While the inhibiting factors are the lack of attention from the government, marketing problems and family problems.Keywords: Community Empowerment, Plastic Waste Recycling Skills